Concentration of angiopoietins 1 and 2 and their receptor Tie-2 in peripheral blood in patients with chronic obstructive pulmonary disease - Kierszniewska-Stępień, Dorota; Pietras, Tadeusz; Ciebiada, Maciej; Górski, Paweł; Stępień, Henryk (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: Both angiopoietins (angiopoietin 1 – Ang-1, angiopoietin 2 – Ang-2) and angiopoietin receptors (Tie) are involved in angiogenesis and vascular remodeling. Aim: To assess concentrations of Ang-1, Ang-2 and Tie-2 in blood of patients with chronic obstructive pulmonary disease (COPD) and evaluate if their concentrations depend on the severity of the disease. Material and methods : Thirty patients with COPD (stage II–IV) and 8 healthy smokers as well as 8 healthy non-smokers were included in the study. Detailed history was taken, physical examination and spirometry tests were done and blood samples were taken for evaluation of serum concentrations of Ang-1, Ang-2 and Tie. Results: Among COPD patients, 8 patients suffered from moderate disease, 8 patients had severe, while 14 patients had very severe disease. The concentrations of Ang-1 and Ang-2 were not significantly greater in patients with COPD than in healthy controls. The highest concentrations of Ang-1 and Ang-2 were observed in patients with moderate COPD, and levels of Ang-2 correlated with Tie-2 in this group of patients. The levels of Ang-1 were the lowest in healthy non-smokers and in patients with severe COPD, where they inversely correlated with Tie-2. The concentrations of Ang-2 were not significantly higher in patients with moderate COPD when compared with those with severe and very severe disease and healthy smokers, and were significantly higher than in healthy non-smokers. Conclusions : It is possible that Ang-1, Ang-2 and Tie-2 play an important role especially in the early stage of COPD but not in the late phase when vascular complications of the disease occur.